Staging architecture: Design of a theatre complex through conversion and additions to an existant church - Aldén, Albin (My University, 2022)
This is a transformation project for the use of a church as both church and theatre. The backstage area and the foyer of the theatre are additions to the church, which itself is used as a more or less ready-made auditorium, with some relatively minor adjustments, thus retaining its usability as a church. The project employs a methodology of staging that draws from the context, which is understood in a very wide sense. It includes the city, the specific church and its history as well as the history of the site and of churches in general. I discuss the future of the churches of Sweden in relation to the theories of Italian architect Aldo Rossi, emphasizing the need for transformation as well as preservation. I propose that churches can be transformed today in continuity with how they’ve historically been transformed, thus preserving a tradition of transformation as opposed to conserving them in their current state. Transformation and multi-purposing of churches becomes a way to preserve them for religious ceremonies. Very few churches are used at full capacity, but almost all of them have at least a small group of devoted members. In terms of property management, this implies that surplus churches need not be sold and completely rebuilt but could be partly rented out. This is the commission that is simulated in the project, one that I would anticipate to become more common than complete sale and reuse of churches for profane purposes only. Architectural practice is understood as the synthesis of a complex and contradictory reality. This project seeks a synthesis between demands of heritage preservation, religious practice and theatre production, convinced that they together can generate a whole that is richer and more culturally relevant than its component parts.
Keywords: Transformation; Theatre; Church; Context; Rossi; Staging; History